Biological markers associated osteoarthritis - Inchai C; Pasuk Mahakkanukrauh (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Osteoarthritis is the most common degenerative joint disease that develops in the elderly. The worldwide prevalence continues to rise, leading to pain and disability in older ages. Osteoarthritis can be diagnosed by using plain film X-ray combined with clinical appearance and structural features. The imbalance between cartilage synthesis and degradation has been explained in the development of osteoarthritis, which is associated with chondrocyte death. There are many cytokines and biological markers related to the disease. The present review provides a background and discusses the known biological markers that are related to developing osteoarthritis. These include advance glycation end products, glutathione and glycosaminoglycans.